Psychological Respons (Anxiety And Depression) and Biological Respons (Cortisol, Ifn-Γ And Tnf-Α) in Ischemic Stroke Patients by Home Care Holistic Model Approach - Luluk Widarti; Moh. Hasan Mahfoed; Kuntoro Kuntoro; Ketut Sudiana (Jurnal Ners, 2012)
Introduction: The patient with stroke often experience on psychological disorder such as anxiety and depression that lead to biologycal aspects such as on cytokin. The objective of the study was to analyse the corelation between psychological respons (anxiety and depression) and biological respons (cortisol, ifn-γ dan tnf-α) in ischemic stroke patients by home care holistic model approach.Method: This study applied an experimental research with quasy experimental design. The study was conducted in the area of Surabaya by selecting ischemic stroke patients after being hospitalised at ”A-Seruni room, Medic IRNA, Dr. Soetomo hospital”. A sample of size 40 was patients divided equally into two groups, control and treatment groups. The treatment and control groups respectively received holistic home care and home care. The depression and anxiety level were measured by using questionnaires and observation technique, while Cortisol level, IFN-γ and TNF-α levels were measured by using ELISA quantitative technique. The data was analyzed by using Levene’s test for homogeneity of variance, t-test and correlation test.Result: The statistical analysis shows there was a significant difference between psychological response in control group after intervension with p = 0.000 for anxiety, and p = 0.000 for depression. For biological response, there is a significant difference p = 0.007 for cortisol and p = 0.000 for TNF-α. However, there is no significant difference in IFN-γ with p = 0.425. The correlation test result shows there was signi fi cant correlations between anxiety and biological responses such as Cortisol with r = 0.724 and p = 0.038; IFN-γ with r = 0.475 and p = 0.034; TNF-α with r = 0.592 and p = 0.006. Furthermore, there was positive correlation between depression and biological responses such as Cortisol with r = 0.705 and p = 0.033; IFN-γ with r = 0.454 and p = 0.044, TNF-α with r = 0.561 and p = 0.010.Conclusion: Holistic home care could improve the psychological responses by decreasing anxiety and depression level and also could improve biological responses by decreasing Cortisol, IFN-γ and TNF-α level in ischemic stroke patients.